ANALISIS PENEGAKAN HUKUM TERHADAP TINDAK PIDANA TIDAK MELAPORKAN PENEMUAN BENDA CAGAR BUDAYA BERDASARKAN UU NO 11 TAHUN 2010 TENTANG CAGAR BUDAYA ( SUATU PENELITIAN DI KOTA BANDA ACEH ) - Muhammad Ryan Rainaldi; Alvi Syahrin; Suhaidi Suhaidi; Muhammad Ekaputra (USU LAW JOURNAL, 2018)
ABSTRACT Indoensia’s legal system is based on the principle of legality, which means that no one can be punished without the force of the existing legislation. In the Act No 11 Year 2010 on Cultural Heritage, it is clear that on Cultural Heritage, there are several articles containing the provisions of criminal sanctions for those violate them. Considering the title and the topic of this research, the discussions of this criminal provision only focus on criminal act of unwilling to report the property of cultural heritage stipulated in Article 23 paragraph (1) and Article 26 paragraph (4) along with Article 102 and Article 103 Act No 11 Year 2010 On Cultural Heritage. Theactionis categorized as criminal acts in Act No 11 Year 2010 on cultural heritage stipulated from Article 101 to Article 112 which states that on Cultural Heritage, there are several articles containing the provisions of criminal sanctions for those who violate them. The obstacles in applying the criminal sanctions towards the act of “unwilling to report” the Discovery of Property of Cultural Heritage in Gampong Pande Banda Aceh are divided into two specific obstacles which are internal and external obstacles. The criminal liability and procedure supposed to be applied towards the act of unwilling to report the discovery of property of cultural heritage occurred in Gampong Pande Banda Aceh which is national Law is not used in handling this case because the Government of Aceh through the Department of Tourism and Culture allows the Banda Aceh citizens to gain profits from the discovery of ancient gold coin in krueng pande to pay zakat based on Aceh Qanun Regulation No 10 Year 2007 on Baitul Mal, article 19 paragraph 8. Thus, the regulation becomes an excuse for the crime in Article 102 and 103 Cultural Heritage Act occurred in Banda Aceh since the validity of Lex Specialis derogate lex generalis, where a special law overrides the common law.   Keywords : Criminal Act, Unwilling to Report, Property of Cultural Heritage